Pendalaman Furūḍul Ainiyah dalam Meningkatkan Pemahaman Religius Siswa Baru Madrasah Diniyah Nurul Jadid Paiton Probolinggo - Rafiqah, Ummi Rifqatur; Hosna, Rofiatul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
In contemporary times, Islamic boarding schools serve as institutions for acquiring religious knowledge. One of the foundational subjects taught in this context is Furūḍul Ainiyah, which encompasses the most essential aspects of religious education. At the Nurul Jadid Islamic Boarding School—an institution that continues to evolve—there exists a non-formal educational body known as Madrasah Diniyah Nurul Jadid. This institution, which operates in coordination with the main boarding school, offers a specific program dedicated to teaching Furūḍul Ainiyah, targeted exclusively at new students. The program is titled “Three-Month FA Deepening for New Santri. To investigate the effectiveness of this program, a qualitative research method was employed, utilizing field study techniques such as observation, interviews, and documentation. Based on the research conducted in alignment with the methodology outlined, the findings reveal that the three-month FA deepening program has a notably positive impact. It has led to observable changes from one student cohort to the next. The program’s main objective is to ensure that new students thoroughly comprehend the teachings conveyed by instructors and mentors over the three-month period. The program’s influence extends beyond academic understanding. It fosters improved behavior among students, enhances their comprehension of religious principles, and encourages them to actively apply these teachings in real-life situations.